SAT0045 11 years' follow-up of a danish 2-year treat-to-target randomized controlled trial in patients with early rheumatoid arthritis: baseline predictors of functional and radiographic outcomes. (15th June 2017) - Hetland, ML; Stengaard-Petersen, K; Junker, P; Lindegaard, H; Ellingsen, T; Pødenphant, J; Skjødt, H; Vestergaard, A; Ejbjerg, B; Jacobsen, S; Krogh, NS; Østergaard, M; et al.
Abstract : Background: Few RCTs have investigated long-term (>10 years (yrs)) outcomes of goal-directed synovitis suppression in early rheumatoid arthritis (RA). The CIMESTRA trial was a 2-year double-blinded Danish multicenter study on aggressive treatment with csDMARDS (methotrexate (MTX) versus MTX and cyclosporine) in combination with intra-articular glucocorticoids (1+2). Disease control after 2 yrs was excellent with $≈ $50% in remission and halted radiographic progression in both groups. We present 11 yr follow-up data. Objectives: The aims were to 1) investigate the clinical and radiographic status and 2) identify baseline predictors of functional status and erosive progression. Methods: Of 160 patients (pts) included, 130 pts also had MRI of the wrist performed at baseline. 17 pts had died since baseline. All living pts were contacted and 120 signed informed consent to participate in a 11 yrs' follow-up visit assessing e.g. treatment, disease activity (DAS28, CRP, 4 variables), physical function (HAQ), X-ray of hands and feet. Baseline MRI was scored by OMERACT rheumatoid arthritis MRI scoring (RAMRIS) system, X-rays by Sharp-van der Heijde total Sharp Score (TSS). Multivariable linear regression analyses of a panel of baseline variables (see foot note in table) with backward selection were performed with HAQ at 11 yrs (HAQ11 ) and radiographic progression since baseline (ΔTSS0–11 ) as dependent variables. Results: 120 of 160 pts (75%) completed the 11 yrs visit. 96 pts with available baseline MRI and X-rays of both time points were included in the prediction models. Withdrawal analysis comparing the 160 pts with the 40 and 64 pts who were not included showed similar baseline characteristics except for higher DAS28 and HAQ score for withdrawers. Follow-up was after 11.6 yrs (10.7–12.2) (median (IQR)). Pts were 63 yrs (55–72) and 70% females. 20% received biologics (+/- csDMARD), 53% csDMARD alone, 27% were in drug free remission. DAS28 was 2.0 (1.5–2.6); pain score: 1 cm (0.3–3); pt. global: 1.1 cm (0.2–2.9); swollen joint count (28SJC): 0 (0–0); tender joint count (28TJC): 0 (0–1). 76% of pts were in DAS28 remission; HAQ-score was 0.25 (0–0.75); ΔTSS0–11 (median (IQR)):4 (0–13); ΔTSS0–11 (mean±SD): 10.9±16.9). The annual progression rate since baseline was median (IQR):0.4 (0–1.1); mean±SD:0.96±1.52. Multivariable linear regression analyses are shown in Table. Conclusions: 11 years after diagnosis 75% were in DAS28 remission. HAQ-score was low, and mean radiographic progression was <1 TSS unit/year. High DAS28 and positive anti-CCP at baseline were independent predictors of poorer functional status. Baseline MRI bone marrow edema and anti-CCP positivity were independent predictors of radiographic progression. References: Arthritis Rheum 2006; 54: 1401–9. Ann Rheum Dis 2008; 67: 815–22. Disclosure of Interest: M. L. Hetland Grant/research support from: AbbVie, BMS, MSD, Pfizer, Orion, Novartis, Biogen, Eli Lilly, K. Stengaard-Petersen: None declared, P. Junker: None declared, H. Lindegaard: None declared, T. Ellingsen: None declared, J. Pødenphant: None declared, H. Skjødt: None declared, A. Vestergaard: None declared, B. Ejbjerg: None declared, S. Jacobsen: None declared, N. S. Krogh: None declared, M. Østergaard Grant/research support from: Abbvie, BMS, Boehringer-Ingelheim, Celgene, Eli-Lilly, Centocor, GSK, Hospira, Janssen, Merck, Mundipharma, Novartis, Novo, Orion, Pfizer, Regeneron, Schering-Plough, Roche, Takeda, UCB, K. Hørslev-Petersen: None declared